Ruskin College Strike, 1909 (1909)
1909 1880-1914 "Ruskin College Strike, 1909" [T0054.jpg], 1909 Ruskin College was founded in 1899 to offer working class adults the opportunity to receive an education equivalent to that provided by Oxford University. In 1908, a group of Ruskin students, dissatisfied with its education policy which they viewed as too pro-establishment and imbued with elements of 'social control', formed the Plebs League. The students revolt was supported by the Principal, Dennis Hird, and following his dismissal the students took strike action, refusing to attend lectures. Hird and the rebellious students finally split with Ruskin and left to form the Central Labour College which moved to London and was financially supported by the South Wales Miners' Federation and the National Union of Railwaymen.